Marketing Analysis of Sancang Type Bonsai Plants in Lamomea Village Konda District South Konawe Regency - Arjun, Arjun; Surni; Muhammad Aswar Limi (International Journal of Technology and Education Research, 2023)
This study aims to (1) determine the marketing channel of sancang bonsai plants in Lamomea Village, Konda Subdistrict, South Konawe Regency, (2) determine the marketing margin of sancang bonsai plants in Lamomea Village, Konda Subdistrict, South Konawe Regency, (3) determine the profit obtained in each marketing channel, (4) determine the efficiency of the marketing channel of sancang bonsai plants in Lamomea Village, Konda Subdistrict, South Konawe Regency. This research was conducted in Lamomea Village, Konda Subdistrict, South Konawe Regency from February to May 2023. This research used descriptive analysis, marketing margin analysis, and marketing efficiency (Farmer's Share). The number of respondents of sancang bonsai plant farmers amounted to 6 people using the census technique, and the collecting trader amounted to 1 person using snowball sampling technique. Based on the results showed that (1) the marketing channel consists of one channel, namely: (a) Farmers® Collectors ®Consumers (2) the marketing margin obtained for small size sancang bonsai plants is IDR.300,000/tree, medium size is IDR.2,000,000/tree, large size is IDR.3,000,000/tree, very large size is IDR.5,000,000/tree. The profit obtained for small size sancang bonsai plants is IDR.120.380/tree, medium size is IDR.1,600,380/tree, large size is IDR.2,100,380/tree, very large size is IDR.3,400,380/tree. The percentage of the share of the price received by sancang bonsai farmers is 56% so that the marketing of sancang bonsai plants in Lamomea Village, Konda District, Konawe Selatan Regency runs efficiently because the proportion of the price received is >50%.